(untitled) (diségno, 2022)
The digitization of architectural archives has opened an evaluation on the contributions that the digital medium can provide in the production, consultation and dissemination of the archival heritage. The Department of Environmental Civil Engineering and Architecture (DICAAR) of the University of Cagliari holds a large collection of drawings and photographic materials that testify the didactic activity of the School of Architecture and reveal the names of generations of architects and engineers trained in Cagliari. Studying and preserving this heritage means first conserving and transmitting the memory of the school in Cagliari, but also exploring new ways to investigate and communicate the hidden meanings of drawings on paper. The paper analyzes the development of a workflow aimed at the digitization, enhancement and dissemination of project drawings carried out by 41 students at the Royal University of Cagliari to be declared a Civil Architect. Made under the supervision of Gaetano Cima, one of the most important figures in the culture of nineteenth-century architectural and urban design in Sardinia, the 41 projects offer the opportunity to investigate the potential of the digital medium in the construction of personalized and multimedia knowledge paths. Through the definition of narrative segments, the study is oriented towards the construction of an archive that becomes a virtual museum, capable of accompanying the public in the ‘visit’ of never built architectures.